The influences of ambient fine particulate matter constituents on plasma hormones, circulating TMAO levels and blood pressure: A panel study in China. (1st March 2022) - Wang, Jiajia; Wu, Shenshen; Cui, Jian; Ding, Zhen; Meng, Qingtao; Sun, Hao; Li, Bin; Teng, Jun; Dong, Yanping; Aschner, Michael; Wu, Shaowei; Li, Xiaobo; et al.
Abstract: Considerable investigations have been carried out to address the relationship between ambient fine particulate matter (PM2.5 ) and blood pressure (BP) in patients with hypertension. However, few studies have explored the influence of PM2.5 and its constituents on Trimethylamine N-oxide (TMAO), an established risk factor for hypertension and cardiovascular disease (CVD), particularly in severely air-polluted areas. To explore the potential impact of PM2.5 constituents on BP, plasma hormones, and TMAO, a panel study was conducted to investigate changes in BP, plasma hormones, and TMAO in response to ambient air pollution exposure in stage 1 hypertensive young adults. Linear mixed effect models were used to estimate the cumulative effects of fine particulate matters (PM2.5 ) and its constituents on BP, plasma hormones and TMAO. We found that one interquartile range (IQR) (35 μg/m 3 ) increase in 0–1 day moving-average PM2.5 concentrations was statistically significantly associated with elevated systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) with estimated values of 0.13 (95% confidence interval (CI): 0.03 to 0.23) mmHg, 0.18 (95% CI: 0.08 to 0.28) mmHg, and 0.17 (95% CI: 0.09 to 0.26) mmHg, respectively. Hormone disturbance in the renin-angiotensin-aldosterone system was also associated with PM2.5 exposure. Elevated TMAO levels with an IQR increase for 0–4, 0–5, 0–6 moving-average concentrations of PM2.5 were found, and the increased values ranged from 26.28 (95% CI: 2.92 to 49.64) to 60.78 (31.95–89.61) ng/ml. More importantly, the PM2.5 -bound metal constituents, such as manganese (Mn), titanium (Ti), and selenium (Se) showed robust associations with elevated BP and plasma TMAO levels. This study demonstrates associations between PM2.5 metal constituents and increased BP, changes in plasma hormones and TMAO, in stage 1 hypertensive young adults. Source control, aiming to reduce the emission of PM2.5 -bound metals should be implemented to reduce the risk of hypertension and CVD. Graphical abstract: Image 1 Highlights: PM2.5 exposure elevated blood pressure among stage 1 hypertensive young adults. PM2.5 exposure increased the serum levels of stress hormones. Mental constituents of PM2.5 consistently associated with elevated blood pressure. PM2.5 and its mental constituents raised circulating TMAO levels.